Risk factors of stigma related to leprosy - A Systematic Review - Adhikari, Bipin; Kaehler, Nils; Raut, Shristhi; Marahatta, Sujan Babu; Ggyanwali, Kapil (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9902 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 3-11